2018
DOI: 10.1001/jamanetworkopen.2018.0802
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Women Physicians Among Authors of Perspective-Type Articles Published in High-Impact Pediatric Journals

Abstract: Key Points Question Are women, who in 2015 made up 61.9% of pediatricians and 53.0% of full-time physician pediatric faculty, underrepresented among physician first authors of perspective-type articles published in the 4 highest-impact general pediatric journals? Findings In this cross-sectional study, women were underrepresented among physician first authors (140 of 336 [41.7%]). Underrepresentation was more pronounced in article categories described as mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
1
3

Year Published

2018
2018
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 113 publications
(112 citation statements)
references
References 39 publications
3
105
1
3
Order By: Relevance
“…The lower representation of female first authors in the CJA is consistent with similar studies in other medical subspecialties such as pediatrics 11 and gastroenterology, 15 and these trends remain pervasive in academic medical publishing. 3,10,12 Similar to our findings, 61% of published articles in the British Journal of Anaesthesia were authored by a male first author and a male last author, 24% by a female first author and a male last author, 8% by a male first author and a female last author, and only 7% by a female first author and a female last author. 10 In a recent study in Anesthesia and Analgesia, a higher proportion of females were first authors of publications in Anesthesiology (32%) and Anesthesia and Analgesia (30%) 11 ; nevertheless, this analysis included more recent articles from 2002 onwards.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The lower representation of female first authors in the CJA is consistent with similar studies in other medical subspecialties such as pediatrics 11 and gastroenterology, 15 and these trends remain pervasive in academic medical publishing. 3,10,12 Similar to our findings, 61% of published articles in the British Journal of Anaesthesia were authored by a male first author and a male last author, 24% by a female first author and a male last author, 8% by a male first author and a female last author, and only 7% by a female first author and a female last author. 10 In a recent study in Anesthesia and Analgesia, a higher proportion of females were first authors of publications in Anesthesiology (32%) and Anesthesia and Analgesia (30%) 11 ; nevertheless, this analysis included more recent articles from 2002 onwards.…”
Section: Discussionsupporting
confidence: 90%
“…We chose to include both original articles and editorial articles specifically to ensure that we examined articles that were both unsolicited and solicited, respectively. We focused on first and last authorship as these positions typically carry the most weight in academic promotions, 12 although first authorship was considered the most objectively important position.…”
Section: Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Do not host men only panels at conferences. Every editorial board needs gender parity and to publish work authored by women (Silver et al 2018a).…”
Section: Physician Sexual Assault: the Moralmentioning
confidence: 99%
“…For example, one study found that women speakers were more frequently introduced by their first names or not called “doctor” during recorded grand rounds [2]. My work with colleagues has found that the important work that women physiatrists are doing is often left out of medical society newsletters [3] and that high‐impact pediatric journals under‐represent women physicians as first authors of perspective‐type articles [4].…”
Section: Introductionmentioning
confidence: 99%